2015
DOI: 10.12659/msm.892121
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Early Onset of Catheter-Related Bloodstream Infection in an Intensive Care Unit in China: A Retrospective Study

Abstract: BackgroundCatheter-related bloodstream infection (CRBSI) is a life-threatening condition encountered in patients with long-term central venous catheter (CVC) indwelling. The objective was to investigate the clinical characteristics, treatment, and prognosis of CRBSI in the intensive care unit (ICU) in a Chinese center, as well as the risk factors for early CRBSI.Material/MethodsA total of 73 CRBSI patients were retrospectively studied in relation to patients’ clinical and epidemiological data, microbiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The current study showed a statistically significant association between the occurrence of CLA-BSI in ICU patients with higher mean APACHE II scores. The current findings agree with those of Fuzheng et al [32]. Therefore, the prevention of CLA-BSI should be a priority in critically ill patients with complicated diseases.…”
Section: Risk Factors For Cla-bsi In Icu Patientssupporting
confidence: 92%
“…The current study showed a statistically significant association between the occurrence of CLA-BSI in ICU patients with higher mean APACHE II scores. The current findings agree with those of Fuzheng et al [32]. Therefore, the prevention of CLA-BSI should be a priority in critically ill patients with complicated diseases.…”
Section: Risk Factors For Cla-bsi In Icu Patientssupporting
confidence: 92%
“…Staphylococcus epidermidis is an important cause of hospital-acquired opportunistic infection, accounting for more than half of implant-associated bacterial infection (1). Recently, S. epidermidis accounted for 19.3% to 30.1% of many catheter-related blood stream infections (CRBSI), caused by the most common implant catheter (2,3). Furthermore, S. epidermidis was also estimated to occur in more than 50% of joint-implant infections (4).…”
Section: Introductionmentioning
confidence: 99%